The audience and reception of the films from the Profil Film Unit in 1982-1989 - Grzechowiak, Jarosław (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The subject of this article is an analysis of the distribution, attendance results and reception of feature films made by the Profil Film Unit in 1982–1989. The Profil Film Unit was the second film group (alongside Iluzjon, headed by Czesław Petelski) to be reactivated by the cinematography management after martial law was declared in Poland. The artistic director of Profil, Bohdan Poręba, enjoyed the trust and support of the Party authorities, linking his allegiance to communist dogma to his activity in the nationalist ‘Grunwald’ Patriotic Association. Profil’s productions were boycotted by a large part of the acting community (also due to an appeal by the Solidarity Stage and Film Artists published in the newspaper “Tygodnik Mazowsze”), and some of the films made by this unit in the 1980s clearly followed the guidelines of the cultural policy of the Polish United Workers’ Party. The following questions will be answered: How did the political circumstances outlined above affect the distribution and reception of the films made by Profil? What attendance results did the films produced by Profil achieve and to what extent did they differ from the cinema ticket revenues of the films produced by other groups? How was the activity of the Profil Film Unit and the financial results achieved evaluated by the Supreme Board of Film Affairs? How were the productions of Profil received by film critics in the daily press and magazines?